Understanding the socioeconomic dimensions of antibiotic resistance: a critical marketing perspective of healthcare stakeholders - Fazle Malik; Arsalan Shahzad; Zahid Mehmood (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the socioeconomic dimensions of antimicrobial resistance, emphasising the risks associated with imprudent use of antibiotics and the consequent emergence of drug-resistant "superbugs.” Method: The study employed constructivist grounded theory to investigate the perspectives of stakeholders, including physicians, patients, pharmacists, sales managers, and Drug Regulatory Authority of Pakistan (DRAP) employees. In-depth interviews were conducted with these stakeholders at their workplaces in 2022 and 2023, and transcripts were meticulously transcribed for analysis. The process of data analysis consists of open coding, then axial coding, and finally, selective coding to integrate categories into theories while the constant comparison of data was exercised to develop a cohesive theory. Results: Data analysis revealed a dominant theme: "Navigating the Socioeconomic Terrain of Antimicrobial Resistance." Subsequently, several categories emerged, such as pharmaceutical marketting transgression, materialism among physicians and marketers, imprudent antibiotic usage, self-medication practices, lack of awareness among patients and the general public, and malpractice by unqualified and illicit practitioners. Conclusion: The results of the study demonstrated that critical marketing could mitigate the socioeconomic repercussions of AMR by encouraging ethical practices among the healthcare stakeholders, and hence benefit the entire society. Keywords: Pharmaceutical Marketing, Ethical Marketing, Critical Theory, Critical Marketing.